The Constitutional Limits of Anti-Trafficking Norms in the Commonwealth Caribbean - Haynes, Jason (Anti-Trafficking Review, 2022)
Trafficking in persons is a crime and a human rights violation that affects most states across the globe, including those in the Commonwealth Caribbean. There- fore, in the last twenty years, governments have rushed to enact anti-trafficking laws with a level of alacrity the international community has never seen before. While the enactment of these laws is both necessary and desirable, some have pushed the limits of what is constitutionally permissible in a free and democrat- ic society. This article demonstrates that some of the prosecution provisions of anti-trafficking norms enacted by Caribbean governments have encroached or threaten to encroach upon the constitutional rights of accused persons. It concludes that unconstitutional provisions of regional anti-trafficking laws need to be addressed by regional governments as a matter of urgency, as they can potentially be challenged by traffickers with the result being that, if successfully challenged, traffickers may escape liability for crimes they have committed on mere technicalities.